Asymmetric Hydrogenation of Quinoxalines Catalyzed by Iridium/PipPhos - Mršić, Nataša; Jerphagnon, Thomas; Minnaard, Adriaan J.; Feringa, Ben L.; de Vries, Johannes G. (Advanced synthesis & catalysis, 2009)
A catalyst made in situ from the (cyclooctadiene)iridium chloride dimer, [Ir(COD)Cl]2, and the monodentate phosphoramidite ligand (S)‐PipPhos was used in the enantioselective hydrogenation of 2‐ and 2,6‐substituted quinoxalines. In the presence of piperidine hydrochloride as additive full conversions and enantioselectivities of up to 96% are obtained.